Evaluasi Serat Sabut Kelapa Sebagai Bahan Penguat Roda Gigi - Nasaruddin, Nasaruddin; Johanis, Alexius Leonardo; Wabang, Jhon Arnoldos; Hattu, Edwin Pieter Dominggus; Abanat, Jufra Daud J. (Politeknik Negeri Jakarta, 2025)
Coconut fiber has great potential as a composite material. This is supported by the abundant availability of coconut fiber waste and its excellent mechanical properties, as evidenced by several studies. Composites made with natural fibers are currently in high demand due to their advantages, including low density, low cost, biodegradability, corrosion resistance, heat resistance, light weight, abundance, renewable energy, and good mechanical properties. The purpose of this study was to obtain the best mechanical properties for composites using coconut fiber as the reinforcement. This study was conducted by varying the coconut fiber reinforcement with several volume fractions: 20%, 30%, 40%, and 50%, with the matrix used being Unsaturated Polyester Resin Yukalac 157 BQTN. The composite manufacturing process used the hand lay-up method with random fiber arrangement. Bending test results showed the highest load at 20% volume fraction of 798 N and a bending strength of 262 N/mm². Meanwhile, the highest impact strength occurred at 50% volume fraction of 0.0472 J/mm².Kata-kata kunci: Penguat, Roda Gigi, Sabut, Kelapa, Komposit